Performance and safety evaluation of a mixed-spectrum reactor design. (April 2019) - Abou-Jaoude, A.; Stauff, N.E.; Erickson, A.
Abstract: Mixed-spectrum reactors (MXR) have been investigated for a wide variety of applications. Typical MXR core designs are based on fast configurations with moderating material inserted within localized regions of the core. Limited analysis has been conducted on assessing important performance and safety aspects. Three main safety-related metrics are devised in this article to validate the feasibility of MXR designs. A long-lived MXR variant was taken as a case study for this analysis. Reactivity feedback mechanisms were evaluated, along with power peaking effects and fast flux damage. Neutron transport simulations found that distortions are manageable in all three areas, with notable improvements in fluence limits and Doppler broadening coefficients. Power peaking effects can be significantly dampened by slight addition of gadolinium in the fuel and by carefully selecting the reflector material.